Effects of neoadjuvant immunotherapy on hearing in patients with head and neck squamous cell carcinoma - Bryce Hambach; Anhelina Bilokon; John Lee; L. Noelle Allemang; Jennifer Chisholm; Chris K. Zalewski; Julie Christensen; Carmen C. Brewer; James L. Gulley; Clint T. Allen; Lisa L. Cunningham; Katharine A. Fernandez (Scientific Reports)
Abstract Immune checkpoint blockade (ICB) is a commonly used treatment modality for cancer with a growing list of oncologic indications. Ototoxicity is a potential immune-related adverse event of ICB treatment, but the risk of hearing loss after ICB remains unknown. This retrospective chart review sought to identify individuals who received ICB and had available audiometric data before and after treatment in order to identify clinically meaningful changes in hearing. This single center, institutional chart review examined hearing function data in patients who underwent audiometry before and after ICB treatment. Measures included pure tone thresholds, distortion product otoacoustic emissions (DPOAEs), tympanometry, and word recognition scores. Ototoxicity was assessed using the American Speech-Language-Hearing-Association (ASHA) and Common Terminology Criteria for Adverse Events (CTCAEv5.0) guidelines where applicable. We identified twelve individuals with newly diagnosed, advanced-stage Head and Neck Squamous Cell Carcinoma (HNSCC) who received neoadjuvant ICB on a clinical trial. Eleven of twelve (92%) patients (8 male, 4 female, age 41–79 years) did not meet criteria for hearing threshold changes. One patient demonstrated a 10 dB shift at two consecutive frequencies in one ear, meeting the minimum ASHA criteria for significant change. Speech audiometry and tympanometry identified no differences in speech understanding or middle ear function pre-and post-treatment. Variations in DPOAE amplitudes were noted, potentially indicating early outer hair cell damage despite stable audiometric thresholds. In this small data set of newly diagnosed advanced-stage HNSCC, there appears to be a low incidence of significant hearing changes following neoadjuvant ICB treatment. Larger, prospective studies with long-term follow-up are needed to evaluate late-onset ototoxicity. Cancer survivors treated with neoadjuvant immune checkpoint blockade for advanced-stage head and neck squamous cell carcinoma (HNSCC) appear to have a low risk of acute hearing loss based on this study. While significant changes in hearing thresholds were not observed, subtle alterations in cochlear outer hair cell function were detected, suggesting the importance of long-term monitoring to capture potential delayed effects on hearing. This insight helps reassure patients about the immediate ototoxic risks while highlighting the need for continued vigilance in hearing assessment during follow-up.